Impact of the alkyl side chain position on the photovoltaic properties of solution-processable organic molecule donor materials. Issue 30 (12th July 2016) - Zhang, J.; Zhu, X. W.; He, C.; Bin, H. J.; Xue, L. W.; Wang, W. G.; Yang, Y. K.; Yuan, N. Y.; Ding, J. N.; Wei, Z. X.; Zhang, Z.-G.; Li, Y. F.
Abstract : Two new compounds with alkyl side chains at different positions have a similar structure, but exhibit different photovoltaic properties. Abstract : Two new A–D–A structured organic molecules with bithienyl-substituted benzodithiophene (BDT) as the core and donor unit, indenedione (ID) as the end group and acceptor unit, 3, 3′′-dihexyl-2, 2′:5′, 2′′-terthiophene (3T(3-Hex)) or 4, 4′′-dihexyl-2, 2′:5′, 2′′-terthiophene (3T(4-Hex)) as the π bridge, BDT-3T(3-Hex)-ID and BDT-3T(4-Hex)-ID, were designed and synthesized. The two compounds with the alkyl side chains at different positions in the π bridge backbone which are applied in solution-processable organic solar cells (OSCs) as donor materials have the same molecular weight and a similar structure, but exhibit different optical and photovoltaic properties. The BDT-3T(4-Hex)-ID film shows a broad absorption band from 400 nm to 750 nm with an absorption peak about 20 nm red-shifted compared to that of BDT-3T(3-Hex)-ID in solution, benefitting from the outward alkyl side chain in its structure. The power conversion efficiency (PCE) of the solution-processed OSC based on a blend of BDT-3T(4-Hex)-ID and PC71 BM (1.25 : 1, w/w) reached 6.55% with a J sc of 10.54 mA cm −2, a V oc of 0.87 V and a FF of 71.4%, under the illumination of AM 1.5, 100 mW cm −2 . In comparison, the PCE of the OSC based on BDT-3T(3-Hex)-ID as the donor is 1.06% under the same experimental conditions.